ARTIFICIAL INTELLIGENCE IN PUBLIC SECTOR AUDITING: OPPORTUNITIES, RISKS, AND ETHICAL CONSIDERATIONS - Theresia Febiengry Sitanala; Adonia Anita Batkunde (Adisam Publisher, 2025)
This study aims to explore the opportunities, risks, and ethical considerations in the application of artificial intelligence (AI) to public sector audit practices using a literature review method. The development of digital technology has driven the adoption of AI as a potential tool for improving efficiency, accuracy, and early detection of fraud and non-compliance in state financial management. Through a review of previous research, this article highlights the potential of AI in expanding audit scope, accelerating data analysis processes, and enhancing the accountability of public institutions. However, significant challenges remain, including the risk of algorithmic bias, limited regulations governing the use of AI, and the potential for diminished auditor independence. Furthermore, ethical aspects such as data protection, transparency in AI-based decision-making, and auditor moral responsibility remain fundamental issues that must be addressed. This study concludes that the use of AI in public sector audits must be placed within a robust governance framework, accompanied by adaptive regulations and clear ethical guidelines to maximize the opportunities generated without compromising the principles of accountability and integrity.